Hearing loss is an early biomarker in APP/PS1 Alzheimer's disease mice. (19th January 2020) - Liu, Yang; Fang, Shu; Liu, Li-Man; Zhu, Yan; Li, Chang-Ri; Chen, Kaitian; Zhao, Hong-Bo
Highlights: APP/PS1 AD mice have progressive, early onset of hearing loss. Hearing loss is detectable at 2-month old prior to other AD phenotypes. Wave IV and V in ABR in APP/PS1 AD mice are minimized. DPOAE is reduced but CM is normal in APP/PS1 AD mice. Abstract: Alzheimer's disease (AD) is a neurodegenerative disease characterized by a progressive loss of memory and cognitive decline. Over the last decade, it has been found that defects in sensory systems could be highly associated with AD. Hearing is an important neural sense. However, little is known about hearing functional changes in AD. In this study, APP/PS1 AD mice (Jackson Lab: Stack No. 004462) were used. Hearing function was assessed by auditory brainstem response (ABR), distortion product otoacoustic emission (DPOAE), and cochlear microphonics (CM) recordings. Wild-type (WT) littermates served as control. We found that APP/PS1 AD mice measured as ABR threshold had hearing loss. The hearing loss appeared at high frequency as early as 2 months old, prior to the reported occurrence of spatial learning deficit at 6–7 months of age in this AD mouse model. The hearing loss was progressive and extended from high frequency to low frequency. At 3–4 months old, the hearing loss appeared in the whole-frequency range. Moreover, the wave IV and V in the super-threshold ABR were eliminated, indicating substantial impairment in inferior colliculus, nuclei of lateral lemniscus, and medial geniculate body in the upper brainstem. DPOAE in APP/PS1 AD mice was also reduced. However, there was no reduction in CM in APP/PS1 mice. These data demonstrate that unlike age-related hearing loss APP/PS1 AD mice have early onset of hearing loss. These data also suggest that hearing function testing could provide a simple, sensitive, non-invasive screen-tool for early detecting AD and localizing lesion.